Efektivitas Masa Penyimpanan Filtrat Daun Jati (Tectona grandis) terhadap Kualitas Pewarna Preparat Telur STH (Soil Transmitted Helminth) - Afiffah Gita Rahmadhani; Dina Afrianti; Djoko Priyatno (Jaringan Laboratorium Medis, 2025)
Soil-Transmitted Helminth (STH) infections such as Ascaris lumbricoides remain a public health concern in Indonesia, necessitating microscopic fecal examinations using high-quality stains. Eosin is commonly used but poses environmental and health risks. Anthocyanins found in teak leaf (Tectona grandis) filtrate offer a safer and more eco-friendly alternative. One factor affecting anthocyanin color stability is storage duration. This study aimed to evaluate the effectiveness of teak leaf filtrate stored for 0, 7, 14, and 21 days on the staining quality of STH egg preparations. This quasi-experimental study used a Posttest-Only Nonequivalent Control Group Design. The samples consisted of 24 Ascaris lumbricoides egg preparations divided into four treatment groups with six replications each. Staining quality was assessed by three validators based on contrast under the microscope, color absorption, and morphological clarity. Data were analyzed using the Kruskal-Wallis test to determine differences in staining quality across storage durations. All preparations showed good staining quality, and no significant differences were found between the storage groups (p-value = 0.383; > 0.05). These results indicate that teak leaf filtrate remains effective for staining STH egg preparations for  up to 21 days of storage, with the best results observed at 7 days after preparation. Further research is recommended to explore this topic more deeply, with attention to laboratory procedures and technical skills.